2018
DOI: 10.17714/gumusfenbil.294719
|View full text |Cite
|
Sign up to set email alerts
|

Ardahan ve Çevresinde Yabani Olarak Yetişen Gilaburu Meyve Ekstraktının, Antimikrobiyal, Antioksidan ve Antimutajenik Aktivitelerinin Araştırılması

Abstract: Bu çalışmada Ardahan ve çevresinde doğal olarak yetişmekte olan Gilaburu meyvelerinin antioksidan özellikleri, farklı mikroorganizmalar üzerindeki antimikrobiyal etkisi ve Ames testi ile antimutajenik etkisi araştırıldı. Antimikrobiyal aktivite testleri esnasında farklı Gr (+) ve Gr (-) bakteriler ile mayalar kullanıldı. Antimutajenik etki çalışmalarında ise AMES/Salmonella Mikrozom testi ile Salmonella typhimurium TA 98 ve TA 100 suşları kullanıldı. Elde edilen verilere göre gilaburu meyvelerinin ağırlığı ort… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
3
0
1
Order By: Relevance
“…Therefore, to our knowledge, the results obtained from this study will contribute to the literature. Various parts of Viburnum sp (especially the fruit part) display antimicrobial activity (Hızlısoy 2009;Cesoniene et al, 2014;Arslan et al, 2018). There seems to be there is no any study on the flower part of Viburnum tinus for their antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, to our knowledge, the results obtained from this study will contribute to the literature. Various parts of Viburnum sp (especially the fruit part) display antimicrobial activity (Hızlısoy 2009;Cesoniene et al, 2014;Arslan et al, 2018). There seems to be there is no any study on the flower part of Viburnum tinus for their antimicrobial activity.…”
Section: Resultsmentioning
confidence: 99%
“…It has been determined that there is an increase in the total chlorophyll density in the leaves due to the reduction of the transpiration area in order to minimize the amount of water caused by the reduction in the leaf surface. They reported that the decrease in the amount of chlorophyll caused by drought stress applications generally causes damage to the chloroplast membrane, and drought stress causes the decrease in chlorophyll a and chlorophyll b content [15][16][17][18].…”
Section: Avalues Of Chlorophyll (Spad) Amount In Leavesmentioning
confidence: 99%
“…Yapılan ön araştırmalar sonucunda anket çalışması, yerel bitkileri etnobotanik olarak günümüzde hala kullanan farklı yaş, cinsiyet ve eğitim durumuna sahip olan 48 kişi ile yüz yüze olarak gerçekleştirilmiştir. Literatürde benzer çalışmalarda da uygulanan anket tekniklerinden faydalanılmıştır (Arslan, 2005;Bağcı vd., 2016;Sağında, 2014).…”
Section: Yöntemunclassified